Praxishandbuch Online - Fundraising Wie man im Internet und mit Social Media erfolgreich Spenden sammelt - Lampe, Björn; Ziemann, Kathleen; Ullrich, Angela (Einzelveröffentlichungen Kulturmanagement und Museum, 2015)
The days of donation boxes are numbered. An increasing number of clubs and associations, projects and foundations no longer wish to (exclusively) collect donations on the street or via post, but rather are looking to collect funds and mobilize supporters in a more affordable and effective way online. In this book, you will find out how that works. Using various practical examples, the fundamentals of successful online fundraising are explained: from user-friendly website design through efficient social media management, up to planning and evaluation of fundraising campaigns.